2014
DOI: 10.1186/s12909-014-0256-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and academic self-perception among international medical students: the role of peer social support

Abstract: BackgroundPsychological distress among medical students is commonly observed during medical education and is generally related to poor academic self-perception. We evaluated the role of peer social support at medical schools in the association between psychological distress and academic self-perception.MethodsAn online survey was conducted in a medical degree program for 138 international students educated in English in the Czech Republic. The Medical Student Well-Being Index was used to define the students’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 46 publications
9
38
0
2
Order By: Relevance
“…A study by Yamada et al (Yamada et al, 2014) indicated that psychological distress and low peer social support synergistically increase the probability of poor academic selfperception among international medical students. Another study demonstrated a higher risk of depression among Korean students reporting low levels of interpersonal support (Jeong et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yamada et al (Yamada et al, 2014) indicated that psychological distress and low peer social support synergistically increase the probability of poor academic selfperception among international medical students. Another study demonstrated a higher risk of depression among Korean students reporting low levels of interpersonal support (Jeong et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Support from friends and family acted as a buffer for trainees, who mentioned drawing on loved ones for practical and emotional support. Social support is known to be an important buffer in coping with stress in medical students,34 35 including International Medical Graduates 3637…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression have been linked to medical students’ vulnerability to stress [16], and higher levels of psychological distress have been linked to decreases in empathy [17], serious thoughts about dropping out of medical school [5], suicidal ideation [5,10], and poor academic performance [18–20]. Previous research has explored student vulnerability to stress [4,21,22], and several studies have documented major stressors for medical students, including academics [15,18], lack of balance [23], relationships [18], poor student guidance/support [23], volume of information [18,23], finances [23], uncertainty of the future [15], lack of time to oneself [18], time and responsibility [23], and the need to succeed [18].…”
Section: Introductionmentioning
confidence: 99%